Prediabetes: prevalence, associations with cardiovascular risk factors and contribution to survival in the Russian population - Yu. A. Balanova; S. A. Shalnova; A. E. Imaeva; V. A. Kutsenko; A. V. Kapustina; S. E. Evstifeeva; G. A. Muromtseva; R. V. Ievlev; R. N. Shepel; O. M. Drapkina (Кардиоваскулярная терапия и профилактика)
Aim. To assess the prevalence of type 2 diabetes (T2D) and prediabetes in the Russian population aged 25-64 years, as well as the association of prediabetes with risk factors (RFs) of noncommunicable disease. To study the contribution of carbohydrate metabolism disorders to mortality and the occurrence of cardiovascular events.Material and methods. We included data from cross-sectional studies ESSE-RF and ESSE-RF2. The final sample included 26418 people (10268 men and 16150 women) who signed informed consent. A modular questionnaire was used. Biochemical parameters were determined in the National Medical Research Center for Therapy and Preventive Medicine with an Abbott Architect c8000 autoanalyzer using diagnostic kits from Abbott Diagnostics (USA). Impaired fasting glycemia (IFG) was defined as a fasting plasma glucose concentration of 6,1-6,99 mmol/L. The presence of T2D was determined by interview and/or fasting plasma glucose ≥7,0 mmol/L. Obesity was defined as a body mass index of ≥30,0 kg/m2. Abdominal obesity was defined as a waist circumference of ≥102 cm in men and ≥88 cm in women. A prospective observation cohort was formed from 14 regions of ESSE-RF and ESSE-RF2 (n=22812). The vital status of each examined person was clarified once every 2 years. Information on fatal and non-fatal events was collected. Statistical processing was performed using the open-source statistical programming language and R environment (version 4.1). Associations were assessed using logistic regression. Kaplan-Meier curves were used to estimate survival. Associations with endpoints were assessed using Cox proportional hazards models.Results. In the Russian population aged 25-64 years, the prevalence of T2D and prediabetes, assessed by IFG, was 6,9% (men — 7,1%, women — 6,7%) and 6,2% (men — 7,7, women — 5,0% (p<0,001)), respectively. Age, low level of education, obesity, including abdominal obesity, hypertension, tachycardia, hyperuricemia and lipid metabolism disorders were significantly associated with prediabetes, and for men, additionally, stress. Prediabetes and T2D demonstrated a significant decrease of survival, including cardiovascular survival, and the occurrence of a composite endpoint. However, multivariate analysis adjusted for sex, age, and region of residence indicates a significant contribution of T2D, but not IFG.Conclusion. To reduce the T2D burden in the Russian Federation, patients with T2D should be identified early and RFs should be controled. Early detection of prediabetes plays a significant role in the prevention of T2D. In addition, T2D and prediabetes have common risk factors, and therefore common ways of prevention.